CHROMIUM AND LEAD REMOVAL USING SYNTHESIZED NANOCRYSTALLINE ZEOLITE - Izarul Machdar (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Zeolite Y nanocrystal was synthesized from a clear solution at temperature of 80-1500C with 6.38 of Si/Al molar ratio by using Aluminum isopropoxide (Al(OiPr)3) and Ludox LS as alumina and silica source, Tetrametylammonium Hidroxide (TMAOH) and Tetrametylammonium Bromide (TMABr) as first and second organic template, respectively. The products were characterised by X-Ray Diffractometer (XRD) and Scanning Electron Microscopy (SEM) to identify the structure and particle sizes. The image measurements of the particle size record that the average particle sizes of FAU-5, FAU-20 and FAU-35 are 116.46 nm, 169.33 nm and 178.12 nm, respectively. Furthermore, 0.5988 g and 0.6001 g of yields with average particle sizes of 116.46 nm and 43.76 nm can be obtained for FAU-5 (single organic template) and FAU-10 (two organic template, TMABr/TMAOH=0.15) samples, respectively. The smallest average particle size observed is 33.87 nm (FAU-15). The synthesised nanocrystalline zeolite Y was applied for Pb(II) and Cr(III) removal and the results show that the nano crystal samples have very good performance. On FAU-37 at 10 ppm, 30 ppm, 50 ppm and 80 ppm of initial concentration, the adsorption of Pb is 23.56 mg/g, 109.71 mg/g, 181.02 mg/g and 231.46 mg/g, respectively at 216 h and adsorption capacities of Cr are 23.18 mg/g, 84.94 mg/g, 109.75 mg/g and 147.37 mg/g.